José Francisco Ibérico and the rescue of our authors - Gonzales Alvarado, Osmar (2006)
It is fair to recognize that the provinces have considerably enriched what we call national culture. Despite Lima's economic and political centralism, many of our great authors come from cities and towns in the interior of the country. However, in the intellectual aspect, centralism manifests itself in the almost inevitable need that many of these authors have had to migrate to the capital and make their careers as such there.